2016
DOI: 10.1080/19439962.2015.1055414
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure and spatial effects on the frequency of cyclist-motorist collisions in the Copenhagen Region

Abstract: Promoting cycling aims at reducing congestion and pollution and encouraging healthy and sustainable lifestyles, but generally clashes with the crash risk perception while riding a bicycle that is still the most significant disincentive to cycling. The current study analyzed the factors contributing to increase crash risk while riding a bicycle by focusing on the variation of 5349 cyclist-motorist collisions within 269 traffic zones in the Copenhagen Region. The model controlled for traffic exposure for both bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
(53 reference statements)
5
8
0
Order By: Relevance
“…Prato et al (2014) found a statistically significant positive coefficient for heavy vehicle volume using bicycle accidents as dependent variable. When a heavy vehicle is involved, injuries to cyclists and pedestrians are likely to be more severe than when it is not involved.…”
Section: Discussionmentioning
confidence: 87%
“…Prato et al (2014) found a statistically significant positive coefficient for heavy vehicle volume using bicycle accidents as dependent variable. When a heavy vehicle is involved, injuries to cyclists and pedestrians are likely to be more severe than when it is not involved.…”
Section: Discussionmentioning
confidence: 87%
“…Of the macrolevel research studies that have focused on cyclist safety, some have studied the bike infrastructure (7-10), whereas others have studied various zonal characteristics, such as the built environment, land use, and the road facility (10)(11)(12)(13)(14). Although these studies have been useful in investigating factors affecting cyclist safety, almost all the studies used proxies for bike exposure, such as the number of bike lane kilometers (12), the modeled bike mode share (13), and the length of roads (11).…”
mentioning
confidence: 99%
“…Bicycle-vehicle accidents in intersections involve various factors related to road users and the built environment [46]. For the purposes of this study, we collected candidate risk factors in traffic and environmental dimensions based on the literature [11][12][13][14][15][16].…”
Section: Candidate Risk Factorsmentioning
confidence: 99%
“…Researchers have identified various risk factors in this context, among which exposure is known to be most important [11,12]. Other risks can mainly be divided into three dimensions: infrastructural, traffic-related, and environmental.…”
Section: Introductionmentioning
confidence: 99%